2011
DOI: 10.1515/bmc.2011.025
|View full text |Cite
|
Sign up to set email alerts
|

Compensated pathogenic deviations

Abstract: Deleterious or ‘disease-associated’ mutations are mutations that lead to disease with high phenotype penetrance: they are inherited in a simple Mendelian manner, or, in the case of cancer, accumulate in somatic cells leading directly to disease. However, in some cases, the amino acid that is substituted resulting in disease is the wild-type native residue in the functionally equivalent protein in another species. Such examples are known as ‘compensated pathogenic deviations’ (CPDs) because, somewhere in the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…However it is not unusual for a deleterious missense mutation in one species to be found as the wild-type residue in orthologs of other species without effecting on the fitness of the latter; this can occur as a result of the phenomenon termed ‘Compensated Pathogenic Deviations'. 29 Our functional studies are therefore a reminder of the caveats of relying on prediction programmes alone to establish the pathogenicity of variants of unknown clinical significance. It will be of particular importance in the future to extend our studies to other ALS-associated LIR mutations of SQSTM1 similarly suggested to be benign.…”
Section: Discussionmentioning
confidence: 99%
“…However it is not unusual for a deleterious missense mutation in one species to be found as the wild-type residue in orthologs of other species without effecting on the fitness of the latter; this can occur as a result of the phenomenon termed ‘Compensated Pathogenic Deviations'. 29 Our functional studies are therefore a reminder of the caveats of relying on prediction programmes alone to establish the pathogenicity of variants of unknown clinical significance. It will be of particular importance in the future to extend our studies to other ALS-associated LIR mutations of SQSTM1 similarly suggested to be benign.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of 3Cnet, the artificial pathogenic-like variants were generated simply by considering the amino acid frequency and the number of gaps. However, a good conservation scoring scheme depends on multiple components, of which the most important include amino acid frequency, residue similarity (biophysical properties), sequence similarity (considering sequence redundancy and MSA depth), the number of gaps in the MSA, and the concept of ‘compensated pathogenic mutations’ (CPDs), which refers to mutations occurring in different species that are tolerated because of compensating mutations 31 . Indeed, it may be possible to exploit the LLR output from ESM-1b to suggest compensatory mutations and use the final VariPred output to evaluate their effect.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of 3Cnet, the artificial pathogenic-like variants were generated simply by considering the amino acid frequency and the number of gaps. However, a good conservation scoring scheme depends on multiple components, of which the most important include amino acid frequency, residue similarity (biophysical properties), sequence similarity (considering sequence redundancy and MSA depth), the number of gaps in the MSA, and the concept of ‘compensated pathogenic mutations’ (CPDs), which refers to mutations occurring in different species that are tolerated because of compensating mutations [39]. Therefore, in the future, it may be worth investigating whether such a combination of data augmentation and synthetic data strategies can further improve the performance of VariPred.…”
Section: Discussionmentioning
confidence: 99%